Problems and solutions in mathematics - Jiang, Guo-Ying; Chen, Ji-Xiu; Pan, Yang-Lian; Qin, Tie-Hu; Tong, Yu-Sun; Wu, Quan-Shui; Xu, Sheng-Zhi (Major American universities Ph.D. qualifying questions and solutions, 1998)
This book presents over 500 mathematical problems and their solutions taken from PhD qualifying exams of leading American universities. Covering six key areas-Algebra, Topology, Differential Geometry, Real Analysis, Complex Analysis, and Partial Differential Equations-it challenges readers to apply deep mathematical understanding and advanced techniques.